Bullying behaviors investigating myths and facts - Sleeth, Shannon; Garner, Simon; Leigh, Richard; Collins, Cath; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2005)
This program explains to students what bullying is and the many different forms it can take. It also provides students with a range of coping mechanisms and strategies
Title from title screen
Executive producer, Mark McAuliffe ; editor, Shannon Sleeth ; sound, Wayne Martin, Alexy Gudimenko ; camera, Peter Zakharov...[et al.]
Voice over: Chrisb Adamidis
Keywords: Bullying in schools; Bullying